1996
DOI: 10.1002/(sici)1096-9861(19960812)372:1<9::aid-cne2>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of single axons of tectospinal neurons in the upper cervical spinal cord

Abstract: Morphology of single axons of tectospinal (TS) neurons was investigated by intraaxonal injection of horseradish peroxidase (HRP) at the upper cervical spinal cord of the cat. TS axons were electrophysiologically identified by their direct responses to stimulation of the contralateral superior colliculus (SC). None of these axons responded to thoracic stimulation at Th2. Three-dimensional reconstructions of the axonal trajectories were made from 20 well-stained TS axons at C1-C3. Cell bodies of these axons were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Physiologically, the deep layers of the SC are responsible for the generation of directed orienting movements, which in cats and rats involve not only eye‐head movements but also movements of the entire body (Syka and Radil‐Weiss, 1971; Harris, 1980; McHaffie and Stein, 1982; Northmore et al, 1988; Dean et al, 1989). These orienting responses can be promoted by neurons of the deep SC through their connections with motor‐related structures in the brainstem, spinal cord, and diencephalon (Chevalier and Deniau, 1984; Redgrave et al, 1986; Yamasaki et al, 1986; Cowie et al, 1994; Muto et al, 1996). In this study, we showed that the type II SNr axons that provide collaterals to the SC also yielded collaterals to the PPTg, suggesting a close functional relationship between these two mesencephalic structures.…”
Section: Discussionmentioning
confidence: 99%
“…Physiologically, the deep layers of the SC are responsible for the generation of directed orienting movements, which in cats and rats involve not only eye‐head movements but also movements of the entire body (Syka and Radil‐Weiss, 1971; Harris, 1980; McHaffie and Stein, 1982; Northmore et al, 1988; Dean et al, 1989). These orienting responses can be promoted by neurons of the deep SC through their connections with motor‐related structures in the brainstem, spinal cord, and diencephalon (Chevalier and Deniau, 1984; Redgrave et al, 1986; Yamasaki et al, 1986; Cowie et al, 1994; Muto et al, 1996). In this study, we showed that the type II SNr axons that provide collaterals to the SC also yielded collaterals to the PPTg, suggesting a close functional relationship between these two mesencephalic structures.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, ϳ60% (27/46) of tectoreticular neurons projecting to the contralateral PPRF were found to send their axons to the spinal cord. Our recent morphological study showed that tectospinal neurons emit multiple axon collaterals in the cervical cord, and spinal interneurons receiving monosynaptic excitation from the contralateral SC directly terminate on neck motoneurons (Muto et al 1996). Therefore the SC could influence neck muscles through such tectoreticulospinal neurons as well as reticulospinal neurons that receive monosynaptic input from the SC (Kakei et al 1994;Sasaki 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The SC of the cat can be divided into three anteroposterior zones from a functional point of view; the anterior, intermediate, and posterior zones (Guitton et al 1980). Tectal output neurons projecting to the spinal cord predominantly exist in the intermediate zone (Muto et al 1996). Therefore tectoreticulospinal neurons in this zone contribute to gaze control by a large-amplitude eye movement and synchronous neck movement to fixate a visual target in the periphery of the visual field (Guitton et al 1980).…”
Section: Discussionmentioning
confidence: 99%
“…All of these sensory signals converge onto the SC in a topographical manner, forming a spatial map (319). The output of the SC is then led to the motor networks in the spinal cord for head and trunk movements to produce the orienting response (226,264). In mammals, the SC output is now connected to the brain stem networks for quick phases (46,102).…”
Section: A Hierarchy Of Oculomotor Mechanismsmentioning
confidence: 99%